Fraudulent Currency Emission in Romanian Law - Rusu, Ion (Acta Universitatis Danubius. Juridica, 2022)
In this paper we analyzed the offence that is mentioned with a marginal title, taking into consideration the provisions in force at this time. We considered elements of identity, as well as of differentiation in relation to previous laws, constitutive content, forms, modalities and some aspects concerning legal precedents and transitory situations. Novelty elements concern both the analysis itself in relation to recent doctrine, as well as recent and relevant case law. Critical analysis of the incrimination text has imposed also critical opinions, supplemented by corresponding de lege ferenda proposals. The paper may be useful both for students of law schools as well as for practitioners in the field of criminal law. This paper is part of a university course to be published at the Universul Juridic publishing house this year.